Stress and polycystic ovarian syndrome-a case control study among Indian women - Jiby Jolly Benjamin; K. MaheshKumar; V. Radha; Karthikeyan Rajamani; Naveen Puttaswamy; Teena Koshy; K.N. Maruthy; R. Padmavathi (Elsevier, 2023)
Background: Polycystic ovarian syndrome (PCOS) is a common hormonal disorder that women belonging to premenopausal age group encounter. Due to its increasing incidence and burden of disease, re-searching the etiopathogenesis of this syndrome is essential and the need of the hour. Recently, the role of stress in the pathogenesis of the syndrome has come into the picture. Hence this study was done to find any significant difference in stress hormone levels between PCOS and healthy controls. Methods: A case-control study was conducted in SRIHER from 2019 to 2021 of which 250 participants were enrolled. Among the 250 subjects, 100 were diagnosed cases of polycystic ovarian syndrome and 150 were healthy women controls. Serum levels of DHEA and Cortisol were measured using ELISA technique and the data obtained was statistically analyzed to check for significance. Results: The serum levels of Cortisol and DHEA were found to be significantly elevated in PCOS compared to healthy women with a statistical significance of p = 0.001 and p = 0.01 respectively. The mean and standard deviation (SD) of Cortisol and DHEA among PCOS women were found to be 395.84 ± 195.62 and 6.04 ± 4.9 respectively. On the other hand, the mean and SD of Cortisol and DHEA among healthy controls were found to 256.26 ± 190.92 and 5.05 ± 3.20 correspondingly. Conclusion: From this study, the stress hormone levels were found to be significantly distinct between the two groups. Stress could play a silent role in the pathogenesis of PCOS and its complications. Interventions to reduce stress among these women can considerably help to reduce the severity of existing symptoms as well as onset of dicey complications.